Using the apparent diffusion coefficient to identifying MGMT promoter methylation status early in glioblastoma: importance of analytical method. Issue 2 (16th April 2015) - Rundle‐Thiele, Dayle; Day, Bryan; Stringer, Brett; Fay, Michael; Martin, Jennifer; Jeffree, Rosalind L.; Thomas, Paul; Bell, Christopher; Salvado, Olivier; Gal, Yaniv; Coulthard, Alan; Crozier, Stuart; et al.
Abstract Introduction Accurate knowledge of O6‐methylguanine methyltransferase (MGMT) gene promoter subtype in patients with glioblastoma (GBM) is important for treatment. However, this test is not always available. Pre‐operative diffusion MRI (dMRI) can be used to probe tumour biology using the apparent diffusion coefficient (ADC); however, its ability to act as a surrogate to predict MGMT status has shown mixed results. We investigated whether this was due to variations in the method used to analyse ADC. Methods We undertook a retrospective study of 32 patients with GBM who had MGMT status measured. Matching pre‐operative MRI data were used to calculate the ADC within contrast enhancing regions of tumour. The relationship between ADC and MGMT was examined using two published ADC methods. Results A strong trend between a measure of 'minimum ADC' and methylation status was seen. An elevated minimum ADC was more likely in the methylated compared to the unmethylated MGMT group (U = 56, P = 0.0561). In contrast, utilising a two‐mixture model histogram approach, a significant reduction in mean measure of the 'low ADC' component within the histogram was associated with an MGMT promoter methylation subtype (P < 0.0246). Conclusion This study shows that within the same patient cohort, the method selected to analyse ADC measures has a significant bearing on the use of that metric as a surrogate marker of MGMT status. Thus for dMRI data to be clinically useful, consistent methods of data analysis need to be established prior to establishing any relationship with genetic or epigenetic profiling.